Trade cooperation in light of the forces that are currently re-shaping international business - Puślecki, Zdzisław W. (Wydział Nauk Politycznych i Dziennikarstwa UAM, 2021)
In this research work, Author focus on the analysis trade cooperation in light of the forces that are currently re-shaping international business. Accordance to the foreign trade policy theory further trade liberalisation and improved framework policies would increase trade and promote growth. It must be emphasized that openess to trade is associated with higher incomes and growth and there are the need for new approaches to trade cooperation. What indicates the importance and innovativeness of the research is the presentation of the new models of the foreign trade policy and trade interests. First of all it must underline that in the new theoretical terms in the demand for trade policy very important is factor specificity. The low specificity of factors means that factor returns are equalized throughout a region’s economy. On the other hand some factors are stuck in their present uses; therefore, factor returns are not equalized throughout a region’s economy, but are industry specific. The main objective of the research task is to give a comprehensive analysis of current trends in foreign trade theory and policy and in particulary the models of foreign trade policy, trade interests indicated by export orientation and import sensitivity, foreign trade policy in different types of authoritarian regimes, protectionistic pressures in different political system, the level of protectionistic pressures, the variation in the foreign trade policy among states, the liberalisation of China foreign trade policy and their effects, the tendencies to international trade liberalisation and the problem of environmental protection, and the tendencies to bilateralism in the foreign trade policy. It should be stressed that free trade in itself is not responsible for economic growth, but more significant are the determining macroeconomic stability and increasing investment.

W tej pracy badawczej, autor koncentruje się na analizie współpracy handlowej w świetle sił, które są obecnie re-shaping międzynarodowego biznesu. Zgodnie z teorią polityki handlu zagranicznego dalsza liberalizacja handlu i ulepszone polityki ramowe zwiększyłyby handel i promowałyby wzrost. Należy podkreślić, że otwartość na handel wiąże się z wyższymi dochodami i wzrostem, dlatego też istnieje potrzeba nowych podejść do współpracy handlowej. Tym, co wskazuje na znaczenie i innowacyjność badań, jest przedstawienie nowych modeli polityki handlu zagranicznego i interesów handlowych. Należy przede wszystkim podkreślić, że w nowych ujęciach teoretycznych w zapotrzebowaniu na politykę handlową bardzo ważne są czynniki specyficzne. Niska specyficzność czynników oznacza, że zwroty czynników są wyrównywane przez gospodarkę regionu. Z drugiej strony niektóre czynniki utknęły w swoich dotychczasowych zastosowaniach, dlatego w takim przypadku zwroty czynników produkcji nie są wyrównywane przez gospodarkę regionu, ale są specyficzne dla danego przemysłu. Głównym celem zadania badawczego jest wszechstronna analiza aktualnych tendencji w teorii i polityce handlu zagranicznego, a w szczególności modeli polityki handlu zagranicznego, interesów handlowych określanych przez orientację eksportową i wrażliwość importową, polityki handlu zagranicznego w różnych typach reżimów autorytarnych, presji protekcjonistycznych w różnych systemach politycznych, poziomu presji protekcjonistycznych, zróżnicowania polityki handlu zagranicznego między państwami, liberalizacji polityki handlu zagranicznego Chin i jej skutków, tendencji do liberalizacji handlu międzynarodowego i problemu ochrony środowiska oraz tendencji do bilateralizmu w polityce handlu zagranicznego. Należy podkreślić, że wolny handel sam w sobie nie jest odpowiedzialny za wzrost gospodarczy, ważniejsze są natomiast czynniki decydujące o stabilności makroekonomicznej oraz zwiększające inwestycje.
Współpraca handlowa w świetle sił modyfikujących współczesny biznes międzynarodowy
Keywords: foreign trade policy; public choice; liberalism; protectionism; autoritarian regimes; bilateralism; polityka handlu zagranicznego; wybór publiczny; liberalizm; protekcjonizm; reżimy autorytarne; bilateralizm